Torino: A Tangible Programming Language Inclusive of Children with Visual Disabilities. (3rd May 2020) - Morrison, Cecily; Villar, Nicolas; Thieme, Anja; Ashktorab, Zahra; Taysom, Eloise; Salandin, Oscar; Cletheroe, Daniel; Saul, Greg; Blackwell, Alan F; Edge, Darren; Grayson, Martin; Zhang, Haiyan
Abstract : Across the world, policy initiatives are being developed to engage children with computer programming and computational thinking. Diversity and inclusion has been a strong force in this agenda, but children with disabilities have largely been omitted from the conversation. Currently, there are no age appropriate tools for teaching programming concepts and computational thinking to primary school children with visual disabilities. We address this gap through presenting the design and implementation of Torino, a tangible programming language for teaching programming concepts to children age 7–11 regardless of level of vision. In this paper, we: (1) describe the design process done in conjunction with children with visual disabilities; (2) articulate the design decisions made; and (3) report insights generated from an evaluation with 10 children with mixed visual abilities that considers how children are able to trace (read) and create (write) programs with Torino. We discuss key design trade-offs: (1) readability versus extensibility; and (2) size versus liveness. We conclude by reflecting upon how an inclusive design approach shaped the final result.